A study to find correlation of platelet indices with HbA1c in diabetic patients with absence/presence of vascular complications - Dubey, Ishan; Gaur, Bindu Singh; Singh, Roma (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes Mellitus is a global pandemic disease. The increased platelet activity is emphasized to play a role in the development of vascular complications of the metabolic disorder. Mean platelet volume (MPV) is an indicator of average size and activity of platelets. This study was conducted to find correlation of platelet indices with HbA1c in diabetic patients with absence/presence of vascular complications. Methods: Total of 100 subjects was enrolled in the study. Sample for glucose estimation and platelet indices were collected and estimation were carried out by the auto-analyzers. The statistical evaluation is done using SPSS version 22. Student t- test was used for doing comparison between two variables namely HbA1c <7 and HbA1c ≥7 and diabetics with vascular complications v/s without vascular complications. Results: MPV, is significantly higher in patients with type -2 diabetes mellitus with HbA1C ≥7 and those with vascular complications in comparison to patients having HbA1c <7 and those without vascular complications ( p- value <0.001 which is highly significant). Conclusions: MPV might be used as a simple and cost-effective laboratory test in the follow up of diabetes mellitus along with HbA1c and thereby help to reduce the morbidity and mortality.